Hydraulic conductivity of bentonite-polymer geosynthetic clay liners to coal combustion product leachates. Issue 5 (October 2021) - Zainab, Binte; Wireko, Christian; Li, Dong; Tian, Kuo; Abichou, Tarek
Abstract: Hydraulic conductivity of seven geosynthetic clay liners (GCLs) to synthetic coal combustion product (CCP) leachates were evaluated in this study. The leachates are chemically representative of typical and worst scenarios observed in CCP landfills. The ionic strength (I) of the synthetic CCP leachates ranged from 50 mM to 4676 mM (TCCP-50, LRMD-96, TFGDS-473, LR-2577, HI-3179 and HR-4676). One of the GCLs contained conventional sodium bentonite (Na–B) and the other six contained bentonite-polymer (B–P) mixture with polymer loadings ranging from 0.5% to 12.7%. Hydraulic conductivity tests were conducted at an effective confining stress of 20 kPa. The hydraulic conductivity of the Na–B GCLs were >1 × 10 −10 m/s when permeated with all six CCP leachates, whereas the B–P GCLs with sufficient polymer loading maintained low hydraulic conductivity to synthetic CCP leachates. All the B–P GCLs showed low hydraulic conductivity (<1 × 10 −10 m/s) to low ionic strength leachates (TCCP-50, I = 50 mM and LRMD-96, I = 96 mM). B–P GCLs with P > 5% showed low hydraulic conductivity (<1 × 10 −10 m/s) up to HI-3179 leachates. These results suggest that B–P GCLs with sufficient polymer loading can be used to manage aggressive CCP leachates. Highlights: Hydraulic conductivity of Na-B and six B-P GCLs to six synthetic CCP leachates. Six synthetic leachates were created in this study to mimic typical to worst field scenarios. B-P GCL with > 5% polymer loading can maintain low hydraulic conductivity to CCP leachates. B-P GCL with sufficient polymer loading can be used to manage aggressive CCP leachates.